AMBITION AS SEEN IN ROBERT LOUIS STEVENSON’S THEMASTER OF BALLANTRAE: A WINTER’S TALE - David Lung; Mister G. Maru; Rinny S. Rorimpandey (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2022)
This research is intended to reveal how a character named James Durie can demonstrate what ambition and causes it. The study uses qualitative research methods. The study also employes a psychological approach and employed the Ludwig Klages the psychological theory of personality and supporting theory about ambitions by Widarso to explain and support the study on an ambition met by a character named James Durie in The Master of Ballantrae: A Winter’s Tale novel. This study suggests that James Durie, as a character capable of meeting all the criteria of his ambition ranging physiological needs, love, honor, position, property and all that he desires must manifest so that, as can be seen by the characteristics of ambitious people in one’s own self-interest, it can be deduced from this study that James Durie or The Master of Ballantrae had the ambition reflected in this novel.